EXPLORING THE AESTHETIC VALUES AND COMPONENTS OF DIGITAL GRAPHIC NOVELS: A SYSTEMATIC REVIEW (Journal of Creative Industry and Sustainable Culture, 2022)
The digital graphic novel (DGN) is a comic book evolution that tells stories in a range of genres. Due to its benefits, DGN has gained a reputation over the years. This paper explores the theoretical parts of DGNs that make them valuable resources for research and infor-mation, identifies the benefits for designers, researchers, and DGN readers. Nonetheless, this study focuses on the aesthetic values and components in designing appealing DGNs. A systematic literature review has been performed on 128 sources. In general, findings from this review have classified five benefits of DGN that impact the educational areas; DGN can encourage learners to read, able to improve critical thinking, serve as a new dimension of learning, build visualliteracy, and able to give positive values in learning. This study sum-marizes the current literature and identified six aesthetic elements and fourteen components that affect the design of DGNs. This study presented a research outline with several oppor-tunities for researchers and practitioners to explore aesthetic values.